How is Piaget's Theory Used to Test The Cognitive Readiness of Early Childhood in School? - Kholiq, Abdul (Indonesian Journal of Early Childhood Education Studies, 2020)
This study aims to examine Piaget's cognitive theory of early childhood readiness to enter elementary school. The method used is quantitative descriptive, using samples of early childhood selected based on the criteria of 5 years of age. The results of the study were processed using statistical calculations. The results obtained were that the instruments developed were effective enough to test cognitive readiness of early childhood in elementary school entrance examinations. In addition, the average tested child has a fairly good readiness but requires guidance by the teacher so that his cognitive abilities develop optimally.